Students' conceptions of simple D.C. electricity circuits: a study of primary, inappropriate conceptions, learning difficulties of physics students, and implications for instruction - Jiya, Zindlovu (Rhodes University, Faculty of Science, Department of Physics, 1990)
The work attempts to identify the general conceptual problems of the generations of Black students who pass through flrst year physics courses at the University of Fort Hare. In particular the alternative conceptions of students in the area of direct current electricity are investigated, using various techniques including written diagnostic tests. The main method used in the investigation of the student frameworks is the personal interview. A varied number of inappropriate conceptions are identifled in the students in significantly large proportions, and these are found to be dependent on many factors; for example the socio-cultural background like language and its metaphors, and media images. It is established that some of these are exacerbated by student perceptions about the nature of physics and of the scientific enterprise in general. Certain proposals are made about how to remedy the situation; relying mainly on the recently established innovative instructional strategies like conceptual change and cognitive conflict, and on making proposals about restructuring certain forms of presentation of the subject matter, paying attention to how language is used to address the speciflc problems of the students. The importance of providing practical experiences for the students is also emphasised
Keywords: Physical sciences -- Study and teaching (Secondary) -- South Africa -- Eastern Cape